Laser ablation synthesis of metal-doped gold clusters from composites of gold nanoparticles with metal organic frameworks - Lukáš Pečinka (Nature Portfolio, 2021)
Abstract Metal-doped gold clusters, mainly cages, are receiving rapidly increasing attention due to their tunable catalytic properties. Their synthesis is mostly based on complex procedures, including several steps. In this work, via adsorption of gold nanoparticles (AuNPs) from aqueous solution to MOF (metal organic frameworks) of M = Co, Cu, Ni, and Zn with various linkers the {AuNPs, MOF} composites were prepared. These composites were used for laser ablation synthesis (LAS) using a common mass spectrometer. Several series of positively and negatively charged Au m M n +/− clusters were observed in mass spectra and their stoichiometry (m = 1–35, n = 1–5) was determined. For each dopant (Co, Cu, Ni, and Zn) ~ 50 different clusters were identified in positive, as well as in negative ion modes. About 100 of these clusters were proposed to be endohedral metal-doped gold cages (for m > 12). The developed approach represents a simple procedure for generating metal-doped gold clusters or endohedral metal-doped gold cages materials with potential applications in medicine and/or electronics.